Recapturing Old England – Nostalgia, Aristo-Anglophilia, and the Historical Roots of ITV’s ‘Downton Abbey’ - Behler, Felix (Interdisciplinary Discourses, Education and Analysis (IDEA))

Fostering students’ peer relationships through the classroom-based intervention FRIEND-SHIP. Education 3-13 - Hassani, S.; Jakob, K.; Schwab, S.; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze (International Journal of Primary, Elementary and Early Years Education.)
Keywords: Life-span and Life-course Studies; Education

Shallow Water DG Simulations on FPGAs: Design and Comparison of a Novel Code Generation Pipeline - Alt, Christoph; Kenter, Tobias; Faghih-Naini, Sara; Faj, Jennifer; Opdenhövel, Jan-Oliver; Plessl, Christian; Aizinger, Vadym; Hönig, Jan; Köstler, Harald (Lecture Notes in Computer Science)

Mutation Tree Reconstruction of Tumor Cells on FPGAs Using a Bit-Level Matrix Representation - Opdenhövel, Jan-Oliver; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies (HEART))

Investigating Deceptive Design in GDPR’s Legitimate Interest - Kyi, Lin; Ammanaghatta Shivakumar, Sushil; Santos, Cristiana Teixeira; Roesner, Franziska; Zufall, Frederike; Biega, Asia J. (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems)

Practice reduces the costs of producing head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Psychological Research)
Abstract Previous research indicates that performing passes with a head fake in basketball leads to increased response initiation times and errors as compared to performing a pass without a head fake. These so-called fake production costs only occurred when not given the time to mentally prepare the deceptive movement. In the current study, we investigated if extensive practice could reduce the cognitive costs of producing a pass with head fake. Twenty-four basketball novices participated in an experiment on five consecutive days. A visual cue prompted participants to play a pass with or without a head fake either to the left or right side. The cued action had to be executed after an interstimulus interval (ISI) of either 0 ms, 400 ms, 800 ms or 1200 ms, allowing for different movement preparation times. Results indicated higher response initiation times (ITs) and error rates (ERs) for passes with head fakes for the short preparation intervals (ISI 0 ms and 400 ms) on the first day but no difference for the longer preparation intervals (ISI 800 ms and 1200 ms). After only one day of practice, participants showed reduced fake production costs (for ISI 0 ms) and were even able to eliminate these cognitive costs when given time to mentally prepare the movement (for ISI 400 ms). Accordingly, physical practice can reduce the cognitive costs associated with head-fake generation. This finding is discussed against the background of the strengthening of stimulus response associations.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Trendbericht Organische Chemie 2023 - Breugst, Martin; Andexer, Jennifer N.; Beil, Sebastian B.; Breinbauer, Rolf; Dumele, Oliver; Ernst, Martin; Gellrich, Urs; Germer, Philipp; Giese, Michael; Gulder, Tobias A. M.; Huy, Peter; Hüttel, Wolfgang; et al. (Nachrichten aus der Chemie)
Abstract Polystyrolproben werden mit Eisen(III)chlorid und weißen LEDs zu Oligomeren und Benzoylprodukten; ein Wolframatkatalysator invertiert die Absolutkonfiguration an sp 3 ‐Kohlenstoffzentren; gelöstes Rätsel um eine symmetrieverbotene konrotatorische 14‐Elektronen‐Elektrocyclisierung; Polycarbonate, die sich ohne Lösungsmittel recyceln lassen: Highlights von Oktober 2021 bis 2022.

Lupane derivatives: Design, isolation, synthesis and evaluation of antiplasmodial activity against Plasmodium falciparum 3D7 strain - Yemback, Pierre; Eyong, Kenneth O.; Efange, Noella M.; Kamdem, Michael HK.; Ndinteh, Derek T.; Odumosu, Patricia O.; Folefoc, Gabriel N.; Ayong, Lawrence; Werner, Thomas (Phytochemistry Letters)
Keywords: T4

Chemoenzymatic Synthesis of Chiral Building Blocks Based on the Kinetic Resolution of Glycerol‐Derived Cyclic Carbonates - Terazzi, Constanza; Spannenberg, Anke; von Langermann, Jan; Werner, Thomas (ChemCatChem)
Abstract The biocatalytic kinetic resolution of cyclic carbonates derived from glycerol is reported. A selection of 26 esterases and lipases was tested for the asymmetric hydrolysis of the model substrate (epichlorohydrin carbonate) in aqueous medium. Among them, Pig Liver Esterase and Novozym® 435 showed the best selectivity with E =38 and 49, respectively. Both enzymes were employed for the conversion of 12 glycerol derivatives under optimized conditions. The resolution of halogenated carbonates afforded the unconverted enantiomer in up to >99 : 1 er . Furthermore, Novozym® 435 was successfully recycled 10 times without significant loss of activity. Upscaling and isolation of the chiral carbonate was also demonstrated. Subsequent conversion of this chiral building block allowed the direct one‐pot synthesis of ( S )‐Guaifenesin, ( S )‐Mephenesin and ( S )‐Chlorphenesin in up to 89 % yield and 94 : 6 er .
Keywords: T1; T4; CSSD

Organocatalytic Stereospecific Appel Reaction - Tönjes, Jan; Kell, Lukas; Werner, Thomas (Organic Letters)
Keywords: T2; CSSD

UpCy: Safely Updating Outdated Dependencies - Dann, Andreas Peter; Hermann, Ben; Bodden, Eric

Deskriptive Statistik - Rumlich, Dominik

Inferenzstatistik - Rumlich, Dominik

Materialitäten virtueller Mode: das Fallbeispiel The Fabricant - Brachtendorf, Charlotte; Behrmann, Helga; Brachem, Judith (Jahrbuch Netzwerk Mode Textil)
Virtual fashion, meaning clothes that exist not as physical textile objects but rather as files is gaining popularity. The Fabricant, a digital-only fashion label from Amsterdam is particularly famous for its creations. Within the fashion industry, virtual fashion is taken as a pioneering innovation that can solve problems such as lacking sustainability and unrealistic bodily ideals precisely because it is understood as immaterial. In contrast, this paper argues that virtual fashion is in fact a material phenomenon. For example, to be perceptible to humans in the first place, virtual fashion depends upon various technologies and devices. These devices are themselves subject to specific non-sustainable production processes. Virtual fashion can further be understood as material insofar that it is almost indistinguishable from other mediatized representations of physical fashion. Lastly, just like its physical counterpart, virtual fashion is bound to human bodies and largely adheres to existing bodily ideals.

Auf Tuchfühlung mit dem Tod. - Brachtendorf, Charlotte

Careful Explanations: A Feminist Perspective on XAI - State, Laura; Fahimi, Miriam (Proceedings of the 2nd European Workshop on Algorithmic Fairness)
Explainable artificial intelligence (XAI) is a rapidly growing research field that has received a lot of attention during the last few years. An important goal of the field is to use its methods to detect (social) bias and discrimination. Despite these positive intentions, aspects of XAI can be in conflict with feminist approaches and values. Therefore, our conceptual contribution brings forward both a careful assessment of current XAI methods, as well as visions for carefully doing XAI from a feminist perspective. We conclude with a discussion on the possibilities for caring XAI, and the challenges that might lie along the way.

Rezension zu: „Going to Extremes in Biblical Rewritings: Radical Literary Retellings of Biblical Tropes” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 145)

Rezension zu: „Lesepraktiken im antiken Judentum. Rezeptionsakte, Materialität und Schriftgebrauch” - Bergmann, Claudia Dorit (Theologische Literaturzeitung)

The Power of Psalms in Post-Biblical Judaism. Liturgy, Ritual and Community

ImPaKT - IKT-befähigte modellbasierte Auswirkungsanalyse in der Produktentwicklung : Schlussbericht zum BMBF-Vorhaben - Gräßler, Iris; Pottebaum, Jens; Wiechel, Dominik; Rarbach, Sven; Jacobs, Georg; Höpfner, Gregor; Menninger, Bastian; Schmitz, Jan Niklas; Holland, Martin; Zeifang, Rainer; Trautheim-Hofmann, Andreas; Grasedieck, Paul; et al.